2013
DOI: 10.1002/ejic.201300662
|View full text |Cite
|
Sign up to set email alerts
|

High‐Pressure Synthesis and Characterization of the Actinide Borate Phosphate U2[BO4][PO4]

Abstract: A new actinide borate phosphate, U2[BO4][PO4], was synthesized in a Walker-type multianvil apparatus at 12.5 GPa and 1000 °C. The crystal structure was determined from single-crystal X-ray diffraction data collected at room temperature. U2[BO4][PO4] crystallizes in the monoclinic space group P21/c with four formula units per unit cell and the lattice parameters a = 854.6(2), b = 775.3(2), c = 816.3(2) pm, and β = 102.52(3)°. The structure consists of double layers of linked uranium–oxygen polyhedra parallel to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Indeed, this seems to extend further with the coerced oligomerisation of building units with the application of pressure and temperature. Another interesting observations seems to be the unexpected flexibility of actinide valence states under pressure, emphasised in uranium studies 12,37,38 where despite beginning with oxidised uranium either reduced forms are found after HP/HT conditions are applied or structure formation seems to diverge from what is expected in ambient pressure studies regarding uranium valence. 63 Generally, it can be observed that HP/HT conditions provide an open playground in which actinide compounds are able to exhibit flexible and exotic structure formation, through the adoption of multiple polymorphs at elevated pressures, exhibit distinctive bonding and polyhedra distortions and sometimes unexpected valence behaviour.…”
Section: Perspectives Challenges and Future Directionsmentioning
confidence: 96%
See 2 more Smart Citations
“…Indeed, this seems to extend further with the coerced oligomerisation of building units with the application of pressure and temperature. Another interesting observations seems to be the unexpected flexibility of actinide valence states under pressure, emphasised in uranium studies 12,37,38 where despite beginning with oxidised uranium either reduced forms are found after HP/HT conditions are applied or structure formation seems to diverge from what is expected in ambient pressure studies regarding uranium valence. 63 Generally, it can be observed that HP/HT conditions provide an open playground in which actinide compounds are able to exhibit flexible and exotic structure formation, through the adoption of multiple polymorphs at elevated pressures, exhibit distinctive bonding and polyhedra distortions and sometimes unexpected valence behaviour.…”
Section: Perspectives Challenges and Future Directionsmentioning
confidence: 96%
“…The complex assemblies for both modules, which are designed for the generation of hydrothermal pressure conditions, are internally heated (graphite or LaCrO 3 heater) and temperature control is conducted using an in situ thermocouple. A comparable setup was used by Huppertz, Hinteregger and coworkers [37][38][39][40] for their high-pressure research on 3d and 4f elements. Hydrothermal conditions ( p < 0.25 GPa, t < 850 °C) with sample quantities of up to 1 gram can be achieved using a cold seal vessel 41 (here water is used as pressure media in an externally heated pressure vessel, often made out of inconel®).…”
Section: Dalton Transactions Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Such studies were performed mainly at relatively low pressures and temperatures. [27][28][29][30][31][32] In this report we present the results of the U-As-Cs oxo-system investigations, aiming to explore the synthetic and coordination chemistry of uranium under extreme (HT/HP) conditions. Herein, we obtained four new uranium(VI) arsenates, Cs 4), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds containing both B–O and P–O groups have been classified into two types in terms of reviews by Kniep et al:5 (1) borophosphates in which a common oxygen atom between the B–O and P–O groups exists and (2) borate–phosphates in which all of the B–O and P–O anionic units are isolated. Whereas hundreds of borophosphate compounds have been reported over recent decades, M 3 (BO 3 )(PO 4 ) (M = Be, Mg, Ba, Zn, and Co),7 SrCo 2 (BO 3 )(PO 4 ),8 Ln 7 O 6 (BO 3 )(PO 4 ) 2 (Ln = La, Pr, Nd, Sm, Gd, and Dy),9 K 3 Ln[OB(OH) 2 ] 2 [HOPO 3 ] 2 (Ln = Yb, Lu),10 Th 2 (BO 4 )(PO 4 ),11U 2 (BO 4 )(PO 4 ),12 Ba 5 [(UO 2 )(PO 4 ) 3 (B 5 O 9 )] · n H 2 O,13 and Mn 3 (OH) 2 [B(OH) 4 ][PO 4 ]14 are the only reported borate–phosphates that we could retrieve. Compared with the hundreds of borophosphates, borate–phosphates are extremely rare.…”
Section: Introductionmentioning
confidence: 99%